The Challenges in Strengthening Standards for Improving the Function of Urban Intersections in Malang - Ahnaf Vansya; Siti Marwiyah; Wahyu Prawesthi; Vieta Imelda Cornelis (UNIVERSITAS PAKUAN, 2026)
Increased urban mobility requires the management of road intersections that is not only technically effective but also has a clear legal basis. The Gunggung, Jalan Raya Langsep, Jalan Dieng, and Jalan Terusan Dieng intersections in Malang City are strategic areas that require a feasibility study on alternative measures to improve intersection functionality. However, traffic management and engineering regulations still leave ambiguities in the norms, particularly regarding the legal basis, feasibility criteria, and the authority of local governments to determine improvements or changes to intersection functions. This study aims to analyze the impact of such regulatory ambiguity on legal certainty in urban traffic engineering policy-making. The method used is normative legal research with a regulatory and conceptual approach. The results of the study indicate that existing regulations have established general objectives for traffic management but have not provided operational, measurable, and binding indicators for determining the feasibility of upgrading intersection functions. In conclusion, it is necessary to strengthen regulations regarding feasibility parameters, assessment procedures, and the division of local government authority so that policies on upgrading intersection functions possess legitimacy, accountability, and legal certainty. Keywords: regulatory ambiguity, traffic engineering, feasibility studies, intersection improvement, local government.